In vitro measurement of ciliary beat frequency in 92 children with recurrent respiratory tract problems. Issue 12 (10th December 2022) - Drake-Lee, A; Green, A; McDermott, A-L
Abstract: Background: Chronic or recurrent mucoid respiratory tract symptoms may be difficult to diagnose. Method: Ninety-two children with chronic respiratory symptoms were divided into 4 groups: 18 children with refractory asthma, 10 with bronchiectasis without dextrocardia, 18 with dextrocardia and 46 with recurrent respiratory tract infections. Except for five neonates, cytology samples were taken under general anaesthesia. Ciliary beat frequency was measured photometrically and analysed by in-house computer software. Results: Nasal polyps were found in one child with normal ciliary beat frequency. Twenty-six children had no beating cilia (male to female ratio, 15:11). The effect of increasing temperature on the ciliary beat frequency of the remaining 66 patients was evaluated (42 patients, more than 30°C, median, 8.3 Hz; 24 patients, 30–37°C, median, 11.8 Hz; p = 0.0003). Conclusion: The measurement of ciliary beat frequency is part of the diagnostic work up of patients with persistent or recurrent respiratory tract infections.